The spatial dimensions of economic development: The case of the upper Midwest - Logan, M.I. (Regional studies, 1970)
Logan M.I. (1970) The spatial dimensions of economic development: The case of the upper Midwest, Reg. Studies 4, 117-125. Few theoretical notions have been developed with reference to regional patterns of economic development. Three hypotheses, however, may be formulated: (1) regional economic development occurs on a number of interpretable dimensions, (2) a region's level of development is associated with its functional integration into the wider economic system and (3) regional development is associated with distance from large urban centres. The study area consists of the states of Minnesota, Wisconsin, and Michigan, the data is for counties and the methodology is principal components analysis and multiple regression analysis. The first hypothesis is verified, the second appears to be supported, but the third, the most important from a spatial viewpoint, is not confirmed.